Trend of breastfeeding and its impact on morbidity in children in a tertiary care hospital in Kathmandu - Bhatta, Anwesh; Basnet, Rydam (Journal of Lumbini Medical College, 2019)
Introduction: WHO advocates for exclusive breastfeeding in infants till 6 months of age. Exclusive breastfeeding has been estimated to reduce 70% of infection related mortality in children. This study aims to elaborate the current trend of breastfeeding and its impact on common infectious morbidities in children. Method: This study was a prospective longitudinal study done at Kathmandu Medical College Teaching Hospital with a sample size of 103 infants. Detailed proforma including sociodemographic data, breastfeeding related data and morbidities were collected at one and half months of life. The patients were followed up at 6 months of age again and the same proforma was again filled up. Statistical analysis was done with SPSS 20.0 and various associations were elucidated. Results: A total of 103 infants were analyzed. Males were 58 in numbers with mean birth weight of the infants being 3048±537 grams. Breast feeding was initiated within an hour in around 37%. At one and half months of age, 63% reported of exclusive breastfeeding which decreased to 23% at 6 months of age. Breastfeeding for at least 45 days decreased the incidence of Acute Respiratory Infections (ARI), Acute Otitis Media (AOM) and diarrheal diseases although statistically significant difference was found with only ARIs. Conclusion: Prevalence of exclusive breastfeeding is low in the study. The study has also shown that breastfeeding significantly reduces incidence of common infectious morbidities in infants. DOI: https://doi.org/10.22502/jlmc.v7i1.262